2008
DOI: 10.3748/wjg.14.1720
|View full text |Cite
|
Sign up to set email alerts
|

Tumor suppressor and hepatocellular carcinoma

Abstract: A few signaling pathways are driving the growth of hepatocellular carcinoma. Each of these pathways possesses negative regulators. These enzymes, which normally suppress unchecked cell proliferation, are circumvented in the oncogenic process, either the over-activity of oncogenes is sufficient to annihilate the activity of tumor suppressors or tumor suppressors have been rendered ineffective. The loss of several key tumor suppressors has been described in hepatocellular carcinoma. Here, we systematically revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
52
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(54 citation statements)
references
References 178 publications
(258 reference statements)
1
52
0
1
Order By: Relevance
“…It has been shown that the activity of more than 20 different TSGs is lost in HCC due to mutations or due to hyper-methylation of their promoters. 24 The TSGs include micro-RNAs which behave as tumor suppressors.…”
Section: Liver Specific Tumor Suppressor Genesmentioning
confidence: 99%
“…It has been shown that the activity of more than 20 different TSGs is lost in HCC due to mutations or due to hyper-methylation of their promoters. 24 The TSGs include micro-RNAs which behave as tumor suppressors.…”
Section: Liver Specific Tumor Suppressor Genesmentioning
confidence: 99%
“…TGF-ß signaling has been implicated in cancer progression among many different types of cancer including hepatocarcinogenesis (22). Several studies have demonstrated that TGF-ß is overexpressed in HCC (23,24).…”
Section: Discussionmentioning
confidence: 99%
“…Liver cancer remains the fifth most common cancer and the third most common cause of cancerrelated death in the world (2). The mechanisms of cancer-related elimination or reduction of tumor suppressor proteins include transcriptional repression of the genes, degradation of proteins, and posttranslational modifications that change biological activities of these proteins (1,3,4). A number of recent papers showed that certain proteins work as oncoproteins and as tumor suppressors depending on cell environment, target genes, and posttranslational modifications (5)(6)(7)(8)(9)(10)(11)(12).…”
mentioning
confidence: 99%